32.9k views
3 votes
2x - 4y = 6
X - 2y = 3
Solve the systems of equation by substitution

2 Answers

2 votes

Answer:

The system has infinitely many solutions.

Explanation:

System of equations given:


$\left \{ {{2x - 4y = 6} \atop {x - 2y = 3}} \right. $

From the system, we know that


x=3+2y

Now let's find
y using
x=3+2y


2x-4y=6


2(3+2y)-4y=6


6+4y-4y=6


6=6

The system has infinitely many solutions:


$\left \{ {{2x - 4y = 6} \atop {x - 2y = 3}} \right. $

If we divide both sides of the first equation by 2,


$\left \{ {{x - 2y = 3} \atop {x - 2y = 3}} \right. $

User Levi H
by
4.9k points
2 votes

Answer:

Infinite number of solutions.

Explanation:

Both of the equations are the same in different form. Therefore, there is an infinite number of solutions.

User Girish Dusane
by
5.2k points